2015
DOI: 10.1186/s13663-015-0393-3
|View full text |Cite
|
Sign up to set email alerts
|

$C^{*}$-Valued contractive type mappings

Abstract: In this paper we generalize the notion of C * -valued contraction mappings, recently introduced by Ma et al., by weakening the contractive condition introduced by them. Using the new notion of C * -valued contractive type mappings, we establish a fixed point theorem for such mappings. Our result generalizes the result by Ma et al. and those contained therein except for the uniqueness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…, ∈ ( ) satisfy ∑ ∞ =1 ‖ ‖ 2 < 1. Later, many authors extend and improve the result of Ma et al For example, in [23], Batul and Kamran generalized the notation of * -valued contraction mappings by weakening the contractive condition introduced by Ma et al (the mapping is called * -valued contractive type mappings) and establish a fixed point theorem for such mapping which is more generalized than the result of Ma et al; in [24], Shehwar and Kamran extend and improve the result of Ma et al [22] and Jachymski [25] by proving a fixed point theorem for self-mappings on * -valued metric spaces satisfying the contractive condition for those pairs of elements from the metric space which form edges of a graph in the metric space. In 2015, Ma and Jiang [26] introduced a concept of *algebra-valued -metric spaces which generalize an ordinary * -algebra-valued metric space and give some fixed point theorems for self-map with contractive condition on such spaces.…”
Section: Introductionmentioning
confidence: 73%
“…, ∈ ( ) satisfy ∑ ∞ =1 ‖ ‖ 2 < 1. Later, many authors extend and improve the result of Ma et al For example, in [23], Batul and Kamran generalized the notation of * -valued contraction mappings by weakening the contractive condition introduced by Ma et al (the mapping is called * -valued contractive type mappings) and establish a fixed point theorem for such mapping which is more generalized than the result of Ma et al; in [24], Shehwar and Kamran extend and improve the result of Ma et al [22] and Jachymski [25] by proving a fixed point theorem for self-mappings on * -valued metric spaces satisfying the contractive condition for those pairs of elements from the metric space which form edges of a graph in the metric space. In 2015, Ma and Jiang [26] introduced a concept of *algebra-valued -metric spaces which generalize an ordinary * -algebra-valued metric space and give some fixed point theorems for self-map with contractive condition on such spaces.…”
Section: Introductionmentioning
confidence: 73%
“…[21], [7] and [26] can be derived from the existing corresponding fixed point theorems in the setting of the standard metric space in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the relation between a metric and a b-metric, Ma and Jiang [20] then generalised the notion of a C * -algebra-valued metric to a C * -algebra-valued b-metric. The classes of C * -algebra-valued metric spaces and C * -algebra-valued b-metric spaces were then studied by Batul and Kamran [7], Shehwar and Kamran [26], Klin-eama and Kaskasem [19], Qiaoling et al [24], Shehwar et al [25], Tianqing [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2014, Ma et al [7] introduced the concept of C * -algebra valued metric space and established some fixed point results. Later, Alsulami et al [32] suggested some remarks on C * -algebras and proved Banach type contraction result, this line of research was continued in (see [8,[10][11][12]31,34,35]).…”
Section: Introductionmentioning
confidence: 99%